The Vanishing Hectare : Property and Value in Postsocialist Transylvania - Verdery, Katherine, 1948- (Book collections on Project MUSE., 2003)
In most countries in Eastern Europe and the former Soviet Union, the fall of communism meant individuals could acquire land. Based on fieldwork between 1990 and 2001, the author explores the importance of land and land ownership in one Transylvanian community.